Ideational metaphor in exposition texts in an EFL textbook and its pedagogical significance - Muhammad Ibnu Mustofa; Gin Gin Gustine (Universitas Syiah Kuala, 2025)
Analytical exposition texts feature causal relationships and nominalization, which can be explored through a grammatical metaphor framework. Despite numerous studies on analytical exposition texts and grammatical metaphors, research on grammatical metaphors in analytical exposition texts in an EFL textbook has not been extensively reported. Through a qualitative research design, particularly qualitative content analysis, this study explored the frequency and variation of ideational metaphors in four selected analytical exposition texts in an EFL textbook for tenth graders of senior high schools in Indonesia. The results show that shift from process to thing occurred most frequently (37%), followed by shift from relator to relator: circumstance (conjunction verb) (15.8%), shift from process to process: quality (13.7%), and shift from thing to thing: class (of things) (13.1%). The other three types of shifts that occurred least frequently are shift from thing to thing: possessor (of thing) (11%), followed by shift from quality to quality: thing (6.8%), and finally, relator to relator: circumstance (conjunction prepositional phrase) (2.6%). The pedagogical implications of this study emphasize the importance of explicit teaching of grammatical metaphor through a genre-based approach. This research offers important contributions to our understanding of EFL teachers in facilitating students with the knowledge of grammatical metaphor and nominalization for better academic writing skills.